Analisis total asset turnover, net profit margin dan devidend payout ratio terhadap harga saham pada perusahaan LQ45 yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2021-2023 - Gery Utomo; Ahmad Muhajir; Tuah Panjaitan (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2026)
This study aims to determine the influence of TATO, NPM, and DPR on stock price in companies that are members of LQ45 listed on the IDX from 2021 to 2023. The total population of this study is 45 companies, while the sample includes 35 companies. The data analysis method used was multiple linear regression, as well as multiple linear tests in SEM (Structural Equation Modeling) and PLS (Partial Least Squares) approach to assess the relationship between several independent variables (X) and one dependent variable (Y). In the use of SmartPls, this analysis includes the SEM-PLS model that breaks down the model into an outer model (which focuses on validity and reliability) and an inner model (which deals with structural models and hypothesis testing). The results of the individual test showed that TATO had an influence on the Stock Price, while NPM had a insignificant influence on the Stock Price and the DPR also had no effect on the Stock Price. Simultaneously, it shows that TATO, NPM and DPR do not affect the Stock Price of LQ45 companies listed on the IDX from 2021 to 2023.